Visual Mismatch Negativity: A Mini-Review of Non-pathological Studies With Special Populations and Stimuli - Czigler, István; Kojouharova, Petia (Frontiers in Human Neuroscience, 2022)
In this mini-review, we summarized the results of 12 visual mismatch negativity (vMMN) studies that attempted to use this component as a tool for investigating differences between non-clinical samples of participants as well as the possibility of automatic discrimination in the case of specific categories of visual stimuli. These studies investigated the effects of gender, the effects of long-term differences between the groups of participants (fitness, experience in different sports, and Internet addiction), and the effects of short-term states (mental fatigue and hypoxia), as well as the vMMN effect elicited by artworks as a special stimulus category.